"More Important than Any Other Funding Instrument". Issue 3 (31st January 2019) - Unknown
Abstract: Having served as the spokesperson for the CRC "Ritual Dynamics" for many years, Indologist Axel Michaels is well acquainted with the special characteristics of these groups – including CRC visits as a form of ritual in themselves. An interview